Expired Fluoxymesterone Drug as Sustainable Corrosion Inhibitor for Mild Steel (MS) in 3 M HCL Solution: Experimental Investigations towards Mitigation of Metal Dissolution - Raghavendra, Narasimha (International Journal of Chemistry and Materials Research, 2019)
The current research presents corrosion inhibition activity of expired Fluoxymesterone drug on the mild steel (MS) in the 3 M HCl solution. The atomic absorption spectroscopy, Tafel polarization and AC impedance spectroscopy studies have been done to verify the corrosion protection efficiency. The surface studies were carried out by scanning electron microscopy (SEM) technique. Atomic absorption spectroscopy results show that, the amount of iron content is low in the presence of corrosion inhibitor when compared with bare system. Tafel plots clearly hint the mixed corrosion inhibition property (inhibition of both anodic and cathodic corrosion process) of expired Fluoxymesterone drug over the MS surface in the acidic environment. From the AC impedance spectroscopy technique, it is observed that, the charge transfer resistance values enhances with a rise in the concentration of the corrosion inhibitor. Surface studies by SEM also support the atomic absorption spectroscopy, potentiodynamic polarization (Tafel plot) and AC impedance spectroscopy results.